1983
DOI: 10.1136/bmj.287.6404.1499
|View full text |Cite
|
Sign up to set email alerts
|

Role of cold and emotional stress in Raynaud's disease and scleroderma.

Abstract: Research on the aetiology of Raynaud's disease and phenomenon has been hindered by the difficulty of provoking attacks in the laboratory. A study was therefore conducted in which digital and ambient temperatures, electrocardiograms, and stress ratings were obtained during ambulatory monitoring in patients with idiopathic Raynaud's disease, Raynaud's phenomenon secondary to scleroderma, and in normal subjects. In Raynaud's disease about one third of the vasospastic attacks were associated with tachycardia and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
2

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 16 publications
2
43
0
2
Order By: Relevance
“…The present data replicate previous findings (6) that patients with primary Raynaud's disease have greater vasoconstrictive responses to a,-and a2-adrenergic agonists in uncooled fingers. Some attacks of Raynaud's disease are triggered by emotional stress (23), which is typically accompanied by catecholamine release (24). Although Raynaud's disease patients do not have consistently higher plasma catecholamine levels than controls (25-27), normal stress-induced catecholamine elevations, acting upon hypersensitive al-and a2-adrenoceptors, would produce greater digital vasoconstriction in the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The present data replicate previous findings (6) that patients with primary Raynaud's disease have greater vasoconstrictive responses to a,-and a2-adrenergic agonists in uncooled fingers. Some attacks of Raynaud's disease are triggered by emotional stress (23), which is typically accompanied by catecholamine release (24). Although Raynaud's disease patients do not have consistently higher plasma catecholamine levels than controls (25-27), normal stress-induced catecholamine elevations, acting upon hypersensitive al-and a2-adrenoceptors, would produce greater digital vasoconstriction in the patients.…”
Section: Discussionmentioning
confidence: 99%
“…It forms part of the fight and flight response that functions to protect an individual from threat, however over-reactive protection defences that create excessive arousal reactions are a risk factor in the development of autoimmunity (e.g., Schore, 1994). It has been suggested that individuals diagnosed with scleroderma have a heightened stress response, when compared to individuals without scleroderma (Freedman & Ianni, 1983). Hyper-arousal is involved in the stress response and autoimmunity (e.g., Every & Lating, 2002) and is higher in individuals who are more physiologically and emotionally reactive (Pfaff, 2005).…”
Section: Background To Scleroderma and Its Impactsmentioning
confidence: 99%
“…Self-compassion reflects an ability to positively regulate emotions that lead to increased feelings of autonomy and the capacity to provide care and compassion for both self and others that are associated with positive health outcomes (Reyes, 2011). Individuals diagnosed with scleroderma tend to have a heightened stress response (Freedman & Ianni, 1983), when compared with individuals without scleroderma. This response is likely to be linked to feelings associated with fear or threat and the ability to self sooth; and may reflect an inability to regulate emotions through insufficient self-compassion.…”
Section: Self-compassion: Biopsychosocial Implicationsmentioning
confidence: 99%
“…Eine Normstichprobe mit einem n = 630 einer deutschen Normalpopulation stand als Kontrollgruppe zur Verfügung (Hampel und Selg, 1975). Normen liegen getrennt für beide Geschlechter und innerhalb der Geschlechter für drei Altersstufen (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Jahre, 31-50 Jahre, über 50 Jahre) vor.…”
Section: Patientenunclassified